PENANGANAN PENYALURAN DORONGAN SEKSUAL REMAJA AUTIS - Sukinah, Sukinah; Alimin, Zaenal; Rochyadi, Endang (Jurnal Penelitian Ilmu Pendidikan, 2015)
This study is set out from the phenomenon of sexual conflict in teenagers with autism. Sexual urge is a natural biological need in a stage of development. For that, we need a wise handling and normatively accepted by society. The wise handling need support from different sources in the community, support of view or perspective that gives the correct solution in handling autistic adolescent sexual urge. The purpose of this study is to find out the preparations both parents and teachers of children with autism to enter adolescence, prevention efforts and treatment that can be done by parents and teachers to the emergence of other forms of sexual behavior of adolescents with autism and the proper sexual urge distribution techniques for autistic adolescent. This study uses a qualitative approach using the Delphi Study. The technique of collecting data through in-depth interviews, observation, Forom Group Discusion (FGD) and documentation with resource parents, teachers, orthopaedagog, psychologist, psychiatrist, doctors and clerics (Islam, Christian, Catholic, Hindu and Buddhist). The data analysis technique used is descriptive analysis, content analysis, taxonomy, domain and traffic perspective. The result shows that the development of adolescence in children with autism generally aged 8-21 years; characteristics of both primary and secondary development are the same as adolescents in general, what distinguishes are the ability of self-control; sexual behaviors that appear to form self-exploration of the opposite sex began to be interested though can not interpret the relationship, a factor that encourages the emergence of sexual behavior in terms of internal (hormonal changes), while the external (the promiscuity, the lack of proper understanding about sex and self-control); forms of sexual behavior does not include sexual deviant behavior due to self control limitations and the ability to communicate; preparation of teachers and parents giving the same treatment as adolescents generally by giving guidance at an early age and assistance at all phases of development, prevention and treatment of sexual behavior can be done through self internal of autistic adolescence itself, external environment and the right distribution of sex drive through marriage with the assistance of older people. Keywords: Sexual Urge Distribution, Autistic Adolescence